2005
DOI: 10.1097/01.crd.0000154790.42283.a1
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA Reductase Inhibitors and Coenzyme Q10

Abstract: The most concerning adverse reaction with HMG-CoA reductase inhibitors (statins) is myotoxicity. Statins inhibit the production of mevalonate, a precursor of both cholesterol and coenzyme Q10, a compound believed to be crucial for mitochondrial function and the provision of energy for cellular processes. There is speculation that a reduction in coenzyme Q10 concentrations may promote the myopathies that have been associated with statin treatment as a result of mitochondrial damage. Although studies have repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 24 publications
1
44
0
2
Order By: Relevance
“…Neither supplementation of plant sterols or stanols nor supplementation with n-3 PUFA had any known clinical significant side effects, although n-3 PUFA supplementation (1) in the mevalonate pathway. The same pathway is shared by coenzyme Q 10 and as a consequence coenzyme Q 10 synthesis is inhibited (2) (112,113) . Coenzyme Q 10 supplements may raise the levels of coenzyme Q 10 (3) in plasma and platelets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neither supplementation of plant sterols or stanols nor supplementation with n-3 PUFA had any known clinical significant side effects, although n-3 PUFA supplementation (1) in the mevalonate pathway. The same pathway is shared by coenzyme Q 10 and as a consequence coenzyme Q 10 synthesis is inhibited (2) (112,113) . Coenzyme Q 10 supplements may raise the levels of coenzyme Q 10 (3) in plasma and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…The only randomised controlled clinical trials investigating this area showed contrasting results and further well-performed clinical trials are needed to investigate whether CoQ 10 can be used to support statin therapy. Although several studies have shown that plasma CoQ 10 levels are decreased after statin therapy, existing evidence also suggests that skeletal muscle CoQ 10 levels are not affected or even increased after statins (113,115,116) .…”
Section: Effects Of Combination Therapy With Coenzyme Q 10 and Statinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The body content of CoQ10 decreased rapidly after the age of 40 years in humans with reduced biosynthesis (Kalen et al, 1989). The CoQ10 supplementation reversed the reduced circulating CoQ10 concentrations in statin-treated subjects as statin inhibits the pathways involved in both cholesterol and CoQ10 supplementation (Nawarskas, 2005;Fedacko et al, 2013). Various authors recommended daily intake of CoQ10 about 30-100 mg for healthy people over 40 years and 60-1200 mg for those undergoing an adjunctive therapy in some medical conditions (Jones et al, 2002, Bonakdar and Guarneri, 2005, Challem, 2005.…”
Section: Coenzyme Q10 Absorption Among Body Tissuesmentioning
confidence: 95%